2017
DOI: 10.3389/fneur.2017.00613
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and Evaluation of an Economic Model for Telestroke: Experience from Virtuall, France

Abstract: BackgroundTelestroke is recognized as a safe and time-efficient way of treating stroke patients. However, admission centers (spokes) are subject to financial charges which can make them reluctant to join the system. We implemented and assessed an economic model supporting our telestroke system, Virtuall, France, which includes one expert center (hub) and six spokes.MethodsThe model is based on payment for the expertise provided by the hub, distribution of charges related to telemedicine according to the fees p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Specifically, within the socio-economic article cluster, two papers implemented costutility analyses [75,76], eight studies employed cost-effectiveness surveys [52,58,60,64,[77][78][79][80], eight conducted cost-benefit analyses [57,74,[81][82][83][84][85], and one utilized the classic cost accounting technique [56]. Cost-benefit analyses were also detected in articles included in the economic cluster [86][87][88][89][90][91][92][93]. In this case, costs and benefits were defined in monetary terms, including via the Net Present Value (NPV), Internal Rate of Return (IRR), and Quality of Service (QoS).…”
Section: Environmentalmentioning
confidence: 99%
“…Specifically, within the socio-economic article cluster, two papers implemented costutility analyses [75,76], eight studies employed cost-effectiveness surveys [52,58,60,64,[77][78][79][80], eight conducted cost-benefit analyses [57,74,[81][82][83][84][85], and one utilized the classic cost accounting technique [56]. Cost-benefit analyses were also detected in articles included in the economic cluster [86][87][88][89][90][91][92][93]. In this case, costs and benefits were defined in monetary terms, including via the Net Present Value (NPV), Internal Rate of Return (IRR), and Quality of Service (QoS).…”
Section: Environmentalmentioning
confidence: 99%
“…Analyses have repeatedly shown that clinical outcomes using telestroke are equal to in-person care and further reduce hospital and societal costs. [62][63][64][65] Telesurgery, or the use of robotics to perform hospital rounds and surgical procedures, is another emerging telemedicine component. 66,67 Currently, nearly 50% of the US population is more than an hour away from tertiary medical centers capable of providing adequate neurosurgical care, rehabilitation, and/or stroke management.…”
Section: Emerging Applications In Telemedicinementioning
confidence: 99%